Integration of spatial distortion effects in a 4D computational phantom for simulation studies in extra‐cranial MRI‐guided radiation therapy: Initial results. Issue 4 (13th December 2020) - Kroll, C.; Dietrich, O.; Bortfeldt, J.; Kamp, F.; Neppl, S.; Belka, C.; Parodi, K.; Baroni, G.; Paganelli, C.; Riboldi, M.
Abstract : Purpose: Spatial distortions in magnetic resonance imaging (MRI) are mainly caused by inhomogeneities of the static magnetic field, nonlinearities in the applied gradients, and tissue‐specific magnetic susceptibility variations. These factors may significantly alter the geometrical accuracy of the reconstructed MR image, thus questioning the reliability of MRI for guidance in image‐guided radiation therapy. In this work, we quantified MRI spatial distortions and created a quantitative model where different sources of distortions can be separated. The generated model was then integrated into a four‐dimensional (4D) computational phantom for simulation studies in MRI‐guided radiation therapy at extra‐cranial sites. Methods: A geometrical spatial distortion phantom was designed in four modules embedding laser‐cut PMMA grids, providing 3520 landmarks in a field of view of (345 × 260 × 480) mm 3 . The construction accuracy of the phantom was verified experimentally. Two fast MRI sequences for extra‐cranial imaging at 1.5 T were investigated, considering axial slices acquired with online distortion correction, in order to mimic practical use in MRI‐guided radiotherapy. Distortions were separated into their sources by acquisition of images with gradient polarity reversal and dedicated susceptibility calculations. Such a separation yielded a quantitative spatial distortion model to be used for MR imaging simulations. Finally, the obtained spatial distortion model was embedded into an anthropomorphic 4D computational phantom, providing registered virtual CT/MR images where spatial distortions in MRI acquisition can be simulated. Results: The manufacturing accuracy of the geometrical distortion phantom was quantified to be within 0.2 mm in the grid planes and 0.5 mm in depth, including thickness variations and bending effects of individual grids. Residual spatial distortions after MRI distortion correction were strongly influenced by the applied correction mode, with larger effects in the trans‐axial direction. In the axial plane, gradient nonlinearities caused the main distortions, with values up to 3 mm in a 1.5 T magnet, whereas static field and susceptibility effects were below 1 mm. The integration in the 4D anthropomorphic computational phantom highlighted that deformations can be severe in the region of the thoracic diaphragm, especially when using axial imaging with 2D distortion correction. Adaptation of the phantom based on patient‐specific measurements was also verified, aiming at increased realism in the simulation. Conclusions: The implemented framework provides an integrated approach for MRI spatial distortion modeling, where different sources of distortion can be quantified in time‐dependent geometries. The computational phantom represents a valuable platform to study motion management strategies in extra‐cranial MRI‐guided radiotherapy, where the effects of spatial distortions can be modeled on synthetic images in a virtual environment.